2001
DOI: 10.1021/jo010307w
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of a Base-Catalyzed Bicyclic Boulton−Katritzky Rearrangement

Abstract: On the basis of quantum chemical calculations, the bicyclic Boulton--Katritzky rearrangement (BKR) has been classified as a pseudopericyclic reaction. Theoretical investigations extend the applicability of the BKR to classes of molecules other than those known from experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…To some extent, the electrophilic amination reactions of anions J (Scheme 8), K (Scheme 9), and M (Scheme 10) presented above resemble the previously investigated S N 2 reactions at sp 2 -hybridized carbon [57][58][59][60][61][62][63] or nitrogen [64] atoms, as well as the Boulton-Katritzky rearrangement [65,66]. Thus, the substitution of the sulfate leaving group by an amidate or thioamidate anion may proceed according to either the S N 2π mechanism (out-of-plane nucleophilic attack) by interacting with the π orbital of the imino group, or S N 2σ mechanism (in-plane attack) where a nucleophile interacts with the σ orbital of the imino nitrogen atom (Figure 9).…”
Section: Reactions With Heterocumulenessupporting
confidence: 68%
“…To some extent, the electrophilic amination reactions of anions J (Scheme 8), K (Scheme 9), and M (Scheme 10) presented above resemble the previously investigated S N 2 reactions at sp 2 -hybridized carbon [57][58][59][60][61][62][63] or nitrogen [64] atoms, as well as the Boulton-Katritzky rearrangement [65,66]. Thus, the substitution of the sulfate leaving group by an amidate or thioamidate anion may proceed according to either the S N 2π mechanism (out-of-plane nucleophilic attack) by interacting with the π orbital of the imino group, or S N 2σ mechanism (in-plane attack) where a nucleophile interacts with the σ orbital of the imino nitrogen atom (Figure 9).…”
Section: Reactions With Heterocumulenessupporting
confidence: 68%
“…[1][2][3][4][5][6][7][8][9][10][11] In this context, it has been pointed out that the fundamental difference among these two topologies is the conservation or not of a cyclic orbital overlap between the orbitals involved in bonding changes at the transition state. Henceforth, the lack of orbital overlap in a pseudopericyclic reaction has significant implications in the global ͑i.e., ther-modynamic͒ and local ͑i.e., selectivity͒ chemistry of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have been published on such processes including those of Narasaka and co-workers who found that substitution at the nitrogen atom of O-protonated oximes may occur easily in an S N 2 manner. [40] Moreover, based on the knowledge of heterocyclic chemistry, the well-known Boulton-Katritzky rearrangement can formally be written as an intramolecular nucleophilic substitution that proceeds according to a unimolecular one-step mechanism, [41][42][43][44] which, in turn, bears a resemblance to the recently investigated vinylic S N 2 reactions at carbon atoms. [45][46][47][48][49][50][51] On the basis of this knowledge, substitution of the sulfate leaving group by the amidate anion at the sp 2 -hybridized N2 nitrogen atom in 2 may proceed either by an S N 2π mechanism (out-of-plane nucleophilic attack) by interacting with the π* orbital of the imino group or by an S N 2σ mechanism (in-plane attack) in which the nucleophile interacts with the σ* orbital of the imino nitrogen of the N-O bond (Scheme 7).…”
Section: Computational Studiesmentioning
confidence: 99%